Peridinin Is an Exceptionally Potent and Membrane-Embedded Inhibitor of Bilayer Lipid Peroxidation - Haley, Hannah M. S; Hill, Adam G; Greenwood, Alexander I; Woerly, Eric M; Rienstra, Chad M; Burke, Martin D (Journal of the American Chemical Society, 2018)
Antilipoperoxidant protein dysfunction is associated with many human diseases, suggesting that bilayer lipid peroxidation may contribute broadly to pathogenesis. Small molecule inhibitors of this membrane-localized chemistry could in theory enable better understanding and/or treatment of such diseases, but currently available compounds have important limitations. Many biological questions thus remain unanswered, and clinical trials have largely been disappointing. Enabled by efficient, building block-based syntheses of three atypical carotenoid natural products produced by microorganisms that thrive in environments of extreme oxidative stress, we found that peridinin is a potent inhibitor of nonenzymatic bilayer lipid peroxidation in liposomes and in primary human endothelial cells. We also found that peridinin blocks monocyte-endothelial cell adhesion, a key step in atherogenesis. A series of frontier solid-state NMR experiments with a site-specifically 13C-labeled isotopolog synthesized using the same MIDA boronate building block-based total synthesis approach revealed that peridinin is completely embedded within and physically spans the hydrophobic core of POPC membranes, maximizing its effective molarity at the site of the targeted lipid peroxidation reactions. Alternatively, the widely used carotenoid astaxanthin is significantly less potent and was found to primarily localize extramembranously. Peridinin thus represents a promising and biophysically well-characterized starting point for the development of small molecule antilipoperoxidants that serve as more effective biological probes and/or therapeutics.